Geohistory of Bátorliget-marsh - Sümegi, Pál; Daniel, Péter; Kovács-Pálffy, Péter; Juhász, Imola; Deli, Tamás; Szántó, Zsuzsa (JOURNAL OF LANDSCAPE ECOLOGY, 2003)
This study details a multidisciplinary palaeoecological and geoarchaeological study of some sedimentary sequences (11 cores and open profiles) from Bátorliget marshy natural conservation area, in the northeastern part of the Great Hungarian Plain (Fig.1.). The principal aim is to review the effects of past human impact on the surrounding environment and reconstruct the ancient environment within natural evolution of vegetation, soil, fauna developments and catchment basin ontogeny from occurring of productive economy using sedimentological, geochemical, isotope geochemical, pollen, seed, macrocharcoal, vertebrate, malacological analysis.During the last full glacial, the majority of the land in northern Europe was covered by extensive ice sheet. In comparison, southern parts of Europe remained unglaciated or slightly glaciated. Thus the analysed region probably provided suitable microenvironments for temperate flora and fauna elements during the last glacial. The palaeoecological records suggest that many of the present temperate European trees, shrubs, herbs and animals survived in refugia in southeastern part of Europe during the last glacial. Our data suggest that one of the sporadic forest refugial spots developed on the analysed region at Bátorliget and some very different forest relict places were formed in the different parts of the Carpathian Basin.According to the geological and palaeontological data, some global climatic and environmental changes developed from the last glacial cold maximum to postglacial time. As an unglaciated region during the last glacial, the Carpathian Basin may have provided an important refuge to temperate flora and fauna, this region (including Hungary) is an important intermediate zone (Fig.1.) between Balkan Peninsula and the western, eastern and northern parts of Europe. As a result of the above, Hungary occupies an important geographical position for European palaeoenvironmentalists and archaeologists, who explore the interactions among the effects of the lateglacial/ postglacial environmental changes and the natural faunal as well as floral expanding processes, furthermore among between diffusion of agricultural activity and spread of different cultures in Europe. This region is important for mapping of both natural and anthropogenic vegetation, fauna and soil histories of Europe. The NE part of the Great Hungarian Plain, as a relatively undisturbed, forested marginal area, is one of the last areas, where several endangered species of the flora and fauna live. These species indicate a special history of fauna and flora of this region. Abundance and actual distribution of these species give opportunity to detect an area of full glacial refugia. According to the former archaeological findings, many of prehistoric sites from Upper Palaeolithic to Middle Age can be found in this region. Consequently we were searching for a small catchment basin of this region, where pollen, Mollusca, charcoal, vertebrate useful for palaeoecological analysis could have preserved.The palaeoecological research was carried out on Bátorliget marsh, a nature reserve area approximately 2 km west of the Hungarian-Romanian border, in the northern edge of the Great Hungarian Plain. This region, named by Nyírség and surrounded by the high ridge of Carpathians (running in NW to SE) and the flat expanses of the Great Hungarian Plain to the West, means a unique geographical position in Europe.It is located in the border of two very different environmental zones, not only in terms of geological situation but in association of ecological zones. Bátorliget marsh represents a combination of fauna and flora characteristic in mountainous regions of the Carpathians and the Great Hungarian Plain. Flora and fauna of the marsh include several species being rare to the Hungarian lowland although widespread in mountain regions. Abundance of floral and faunal species, which are normally found in wooded areas of the Carpathians, is also extremely high (Nyilas and Sümegi 1991).This study presents the results of a multidisciplinary palaeoecological and geoarchaeological study, which was conducted in order to reconstruct the late Quaternary environmental history and prehistoric human impact of the Great Hungarian Plain, and which was based on palaeoecological and geoarchaeological results (although a part of these results was published in a paper – WILLIS et al. 1995). The methods of geomorpho- logic, sedimentological, geochemical, scanning electron microscope with microsonda (EDAX), pollen, charcoal, molluscan, vertebrate analyses along with radiocarbon dating and stable isotope analysis revealed two sedimentary sequences extending well back into the last glacial.
Keywords: environmental reconstruction; holocene; Mollusca; palynology; sedimentology; refugia